Contributions of Nursing Professionals and Primary Care Physicians in Interdisciplinary Oncology Teams for Cancer Pain Management: An Analytical Review - Henry Riyanto Sofyan; Anne Dina Soebroto; Eunike Novrilia; Ratu Novia Putri Aulia; Daniel Budi Utomo; Liliana Mangkuwerdojo; Erico Mulfiardi; Radja Buntal Sotarduga Simanjuntak; Made Agus Mahendra Inggas (Universitas Pelita Harapan, 2026)
Introduction: Cancer-related pain remains inadequately managed in a substantial proportion of oncology patients, despite established clinical protocols. Current systematic evidence indicates that up to 55% of patients experience undertreated pain.35 Interdisciplinary oncology teams — comprising nursing professionals and primary care physicians (PCPs) — are a critical organizational strategy for improving cancer pain management across the care continuum. Methods: A systematic narrative synthesis was conducted using 30 peer-reviewed sources identified through structured searches of the PubMed, CINAHL, Scopus, and Cochrane databases. Inclusion criteria encompassed studies, reviews, and guidelines published from 2002 to 2025 that addressed professional roles, team structure, barriers, and clinical outcomes in cancer pain management. Results: Nursing professionals contribute substantially to pain assessment and management through validated instruments, pharmacological and non-pharmacological interventions, patient self-management education, and interdisciplinary advocacy. PCPs facilitate care coordination, ensure analgesic prescribing continuity, and manage the primary–specialty interface. Effective interdisciplinary teams improve patient outcomes through structured communication, clear roles, and integrated care pathways. Persistent barriers include care fragmentation, professional role ambiguity, competency gaps, and regulatory constraints on opioid prescribing. Conclusions: Although current evidence supports the effectiveness of interdisciplinary approaches to improving cancer pain outcomes, significant gaps remain in comparative effectiveness data, implementation science, and health equity research. Enhanced clinical training, organizational investment, and policy reform are necessary to optimize collaborative cancer pain management across diverse healthcare settings. Keywords: Cancer Pain, Interdisciplinary Teams, Nursing Professionals, Primary Care Physicians, Collaborative Care, Palliative Care, Pain Mechanisms